PENGUATAN LITERASI MATEMATIKA DAN KARAKTER ISLAMI MELALUI PEKAN OLAHRAGA DAN SENI (PORSENI) BAGI SISWA SD 057 PULLIWA - Junaedi; Abdul Wahab; Ayyub Daeng Pananrang; Yulmiati Yulmiati (Sekolah Tinggi Ilmu Kesehatan Bina Bangsa Majene, 2026)
Introduction: Mathematical literacy and the strengthening of Islamic character are essential components in developing both academic competence and moral values among elementary school students. However, mathematics learning is often perceived as abstract and less contextual, while the integration of Islamic values into learning activities has not been optimally implemented. The Sports and Arts Week (Pekan Olahraga dan Seni/Porseni) has the potential to serve as an enjoyable, contextual learning medium as well as a platform for strengthening Islamic character education. Methods: This study employed a qualitative descriptive approach involving students of SD 057 Pulliwa, teachers, and Porseni organizing committees as research participants. Data were collected through observation, in-depth interviews, and documentation during the implementation of Porseni activities. Data analysis was conducted through data reduction, data display, and conclusion drawing, with data validity ensured through source and technique triangulation. Results: The findings indicate that Porseni activities contributed to the strengthening of students’ mathematical literacy through competition-based activities that required counting, measurement, classification, and contextual problem-solving skills. In addition, the internalization of Islamic character values such as sportsmanship, honesty, cooperation, discipline, and responsibility was evident in students’ attitudes and behaviors throughout the activities. Students demonstrated high enthusiasm and active participation in all competitions. Discussion: The integration of mathematical literacy and Islamic character through Porseni provides meaningful and holistic learning experiences. This approach not only enhances students’ cognitive abilities but also fosters moral and character development aligned with Islamic values. Therefore, Porseni can be considered an alternative strategy for learning innovation and character education in elementary schools.